ANALISIS DAN MITIGASI RISIKO PEMBANGUNAN GEDUNG MALL PELAYANAN PUBLIK KABUPATEN GIANYAR - Diputera, I Gede Angga; Lestari, I Gusti Agung Ayu Istri; Utama, I Putu Rika Agus (Fakultas Sains dan Teknologi Universitas Ngurah Rai, 2024)
Risk management is a structured step in examining risks and how to deal with them properly. The greater the value of the project will influence the risk or probability that will occur on a project itself. Gianyar District Public Service Mall Building Development Project is currently in the tender process which is an initial stage before implementing the construction process of a project. The project has a high contract value so there is a possibility of risks arising in the process of its implementation. The aim of this research is to be able to identify, evaluate, and study how to manage the risks arising from the implementation of the project. The phase in analyzing the data in this study is from the collection of data in the form of types of risk from the previous study of risk data from similar projects and then conducting interviews with the parties involved in the Project Development of the Public Service Mall Building District of Gianyar to determine any risks identified from 12 sources of risk. The following is the dissemination of a questionnaire with the number of respondents as many as 30 people involved in the project. Based on the identified risks, the risk assessment and acceptance analysis carried out showed that no risks were classified as unacceptable and one risk went into the unwanted level. Dominant risk control is controlled by establishing risk accountability and implementing risk reduction measures.